Ag nanoparticles supported on a resorcinol-phenylenediamine-based covalent organic framework for chemical fixation of CO2 - Chakraborty, Debanjan; Shekhar, Pragalbh; Singh, Himan Dev; Kushwaha, Rinku; Vinod, C. P.; Vaidhyanathan, Ramanathan (Chemistry-An Asian Journal, 2019)
Covalent organic frameworks are a new class of crystalline organic polymers possessing a high surface area and ordered pores. Judicious selection of building blocks leads to strategic heteroatom inclusion into the COF structure. Owing to their high surface area, exceptional stability and molecular tunability, COFs are adopted for various potential applications. The heteroatoms lining in the pores of COF favor synergistic host-guest interaction to enhance a targeted property. In this report, we have synthesized a resorcinol-phenylenediamine-based COF which selectively adsorbs CO2 into its micropores (12 angstrom). The heat of adsorption value (32 kJ mol(-1)) obtained from the virial model at zero-loading of CO2 indicates its favorable interaction with the framework. Furthermore, we have anchored small-sized Ag nanoparticles (approximate to 4-5 nm) on the COF and used the composite for chemical fixation of CO2 to alkylidene cyclic carbonates by reacting with propargyl alcohols under ambient conditions. Ag@COF catalyzes the reaction selectively with an excellent yield of 90 %. Recyclability of the catalyst has been demonstrated up to five consecutive cycles. The post-catalysis characterizations reveal the integrity of the catalyst even after five reaction cycles. This study emphasizes the ability of COF for simultaneous adsorption and chemical fixation of CO2 into corresponding cyclic carbonates.
Keywords: CO2 capture; covalent organic frameworks; cyclic carbonates; Propargyl alcohols; silver nanoparticles

Exceptional capacitance enhancement of a non-conducting COF through potential-driven chemical modulation by redox electrolyte - Kushwaha, Rinku; Haldar, Sattwick; Shekhar, Pragalbh; Krishnan, Akshara; Saha, Jayeeta; Hui, Pramiti; Vinod, Chathakudath Prabhakaran; Subramaniam, Chandramouli; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2021)
Capacitors are the most practical high-storage and rapid charge-release devices. The number of ions stored per unit area and their interaction strength with the electrode dictates capacitor-performance. Microporous materials provide a high storage surface and optimal interactions. Adsorbing electron-rich and easily polarizable molecules into microporous electrodes is expected to boost Faradaic pseudo-activity. If such electrode-electrolyte interactions can be made as a potential-driven reversible process, the resulting capacitors would be adaptable and device-friendly. A composite covalent organic framework (COF)-carbon electrode with redox-active KI is combined in an H2SO4 electrolyte for the first time. This composite electrode benefits from the redox-functionality of COF and electronic conductivity of carbon, leading to superior capacitative activity. Operando spectro-electrochemical measurements reveal the existence of multiple polyiodide species, although the I-3(-) is the predominantly electroactive species adsorbing on the microporous triazine-phenol COF electrode. A systematic fabrication of the flexible solid-state devices using the COF-redox-electrolyte reveals a high areal capacitance of 270 +/- 11 mF cm(-2) and gravimetric capacitance of 57 +/- 8 F g(-1). The inclusion of KI in H2SO4 (electrolyte) yields an approximately eight-fold enhancement in solid-state gravimetric specific capacitance. The imine-COF retains 89% of its capacity even after 10 000 cycles.
Keywords: covalent organic frameworks; polyiodide; redox electrolytes; solid‐ state capacitors; Supercapacitors

Covalent organic framework with electrodeposited copper nanoparticles - a desirable catalyst for the Ullmann coupling reaction - Chandran, Chandana; Singh, Himan Dev; Leo, Liya S.; Shekhar, Pragalbh; Rase, Deepak; Chakraborty, Debanjan; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (Journal of Materials Chemistry A, 2022)
A covalent organic framework is a porous covalently-linked polymeric assembly built from molecular lego blocks, the monomers. A COF's high surface area, ordered pores, and intrinsic low density makes it a perfect heterogeneous catalyst component. Dispersing catalytic metal nanoparticles into the porous COF matrix in a `capping-agent-free' manner can aid the maximal utilization of the active sites. To generate single-site catalysts, metals have been anchored to dense supports, or metal ions have been coordinated to the porous organic framework. The latter has superior atom efficiency and a substrate diffusion advantage. Stably nestling neutral metallic clusters into open-framework supports with no specifically strong binding groups requires a different approach. If infused from extremely dilute electrolytes, metal clusters can be nanoconfined into electrically activated COFs. At low-loadings, it can resemble a single-site catalyst with high atom efficiency. Herein, we report the larger scale synthesis of IISERP-COF15 and electrochemical loading of copper nanoparticles into its pores at loadings as low as 3.34 wt%. We employed classical Ullmann reactions to adjudge its activity. Typical turnover numbers for the catalysts reported in the literature are approximately 50-100. A Cu@COF shows high activity with a very low catalyst loading of 0.25 mol% (TON around similar to 300-350 vs. 4 for neat CuCl2 center dot 2H(2)O (homogeneous catalyst) and turnover frequency (similar to 15-17 h(-1))). We recycled it for up to 3 cycles. Furthermore, we report a multi-fold Ullmann reaction producing an unreported hexaaldehyde to demonstrate the latitude of the catalyst. Our work points to the potential of a dilutely loaded metal@COF as a mimic of the single-site catalyst for synthesizing valuable C-O linked molecules. Our findings from computational modeling shed light on the role of the COF as an active nanoporous support for Ullmann C-O coupling.

Incorporating conducting polypyrrole into a polyimide COF for carbon-free ultra-high energy supercapacitor - Haldar, Sattwick; Rase, Deepak; Shekhar, Pragalbh; Jain, Chitvan; Vinod, Chathakudath Prabhakaran; Zhang, En; Shupletsov, Leonid; Kaskel, Stefan; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2022)
Redox-active covalent organic frameworks (COFs) store charges but possess inadequate electronic conductivity. Their capacitive action works by storing H+ ions in an acidic electrolyte and is typically confined to a small voltage window (0-1 V). Increasing this window means higher energy and power density, but this risks COF stability. Advantageously, COF's large pores allow the storage of polarizable bulky ions under a wider voltage thus reaching higher energy density. Here, a COF-electrode-electrolyte system operating at a high voltage regime without any conducting carbon or redox active oxides is presented. Conducting polypyrrole (Ppy) chains are synthesized within a polyimide COF to gain electronic conductivity (approximate to 10 000-fold). A carbon-free quasi-solid-state capacitor assembled using this composite showcases high pseudo-capacitance (358 mF cm(-2)@1 mA cm(-2)) in an aqueous gel electrolyte. The synergy among the redox-active polyimide COF, polypyrrole and organic electrolytes allows a wide-voltage window (0-2.5 V) leading to high energy (145 mu Wh cm(-2)) and power densities (4509 mu W cm(-2)). Amalgamating the polyimide-COF and the polypyrrole as one material minimizes the charge and mass transport resistances. Computation and experiments reveal that even a partial translation of the modules/monomers intrinsic electronics to the COF imparts excellent electrochemical activity. The findings unveil COF-confined polymers as carbon-free energy storage materials.
Keywords: carbon free capacitors; cation-anion co-storage; conductivity; high energy capacitors; polypyrrole doped COFs

Synergistic electronic effects in AuCo nanoparticles stabilized in a triazine-based covalent organic framework: a catalyst for methyl orange and methylene blue reduction - Devulapalli, Venkata Swaroopa Datta; Kushwaha, Rinku; Ovalle, Edwin; Singh, Himan Dev; Shekhar, Pragalbh; Chakraborty, Debanjan; Vinod, Chathakudath Prabhakaran; Vaidhyanathan, Ramanathan; Borguet, Eric (ACS Applied Nano Materials, 2022)
Developing stable active catalysts for reducing water-soluble pollutants is a desirable target. In this pursuit, we have functionalized covalent organic frameworks (COFs) with gold (Au) and cobalt (Co) nanoparticles via a one-step aqueous synthesis process, and their catalytic activity in reducing methyl orange and methylene blue is examined. Operando absorbance measurements of methyl orange (anionic dye) reduction revealed AuCoCOF (1.3 Au/1.0 Co) to have superior kinetics over many other catalysts, which typically require additional external stimuli (e.g., photons) and higher catalyst loadings. After confirming the homogeneous dispersion of the nanoparticles on the COF support using three-dimensional (3D) tomography and material stability through powder X-ray diffraction (PXRD), infrared (IR), and thermal studies, we investigated their redox activity. Cyclic voltammetry (CV) confirmed the involvement of both metals in the redox process, while spectroelectrochemical measurements show that their activity and kinetics remain unaltered by an applied potential. Solid-state UV measurements reveal that the neat COF is a semiconductor with a large band gap (2.8 eV), which is substantially lowered when loaded with cobalt nanoparticles (2.2 eV for CoCOF). The electronic synergy between Au and Co nanoparticles further reduces the band gap of AuCoCOF (1.9 eV). Thus, there is a definite advantage in doping non-noble metal nanoparticles into a noble metal lattice and nanoconfining them into a porous COF support. Our study highlights the significance of bimetallic COF-supported nanocatalysts, wherein one can engage each component toward targeted applications that demand redox activity with favorable kinetics.
Keywords: AuCoCOF; band gaps; Covalent organic framework; methyl orange reduction; Nanoparticles; UV-vis spectroscopy

COF-supported zirconium oxyhydroxide as a versatile heterogeneous catalyst for Knoevenagel condensation and nerve agent hydrolysis - Shekhar, Pragalbh; Devulapalli, Venkata Swaroopa Datta; Reji, Reshma; Singh, Himan Dev; Jose, Aleena; Singh, Piyush; Torris, Arun; Vinod, Chatakudath P.; Tokarz III, John A.; Mahle, John J.; Peterson, Gregory W.; Borguet, Eric; et al. (iScience, 2023)
A composite of catalytic Lewis acidic zirconium oxyhydroxides (8 wt %) and a covalent organic framework (COF) was synthesized. X-ray diffraction and infrared (IR) spectroscopy reveal that COF's structure is pre-served after loading with zirconium oxyhydroxides. Electron microscopy confirms a homogeneous distri-bution of nano-to sub-micron-sized zirconium clusters in the COF. 3D X-ray tomography captures the micron-sized channels connecting the well-dispersed zirconium clusters on the COF. The crystalline ZrOx(OH)(y)@COF's nanostructure was model-optimized via simulated annealing methods. Using 0.8 mol % of the catalyst yielded a turnover number of 100-120 and a turnover frequency of 160-360 h(-1) for Knoevenagel condensation in aqueous medium. Additionally, 2.2 mol % of catalyst catalyzes the hy-drolysis of dimethyl nitrophenyl phosphate, a simulant of nerve agent Soman, with a conversion rate of 37% in 180 min. The hydrolytic detoxification of the live agent Soman is also achieved. Our study unveils COF-stabilized ZrOx(OH)(y) as a new class of zirconium-based Lewis + Bronsted-acid catalysts.

Hydroxide ion-conducting viologen-bakelite organic frameworks for flexible solid-state zinc-air battery applications - Rase, Deepak; Illathvalappil, Rajith; Singh, Himan Dev; Shekhar, Pragalbh; Leo, Liya S.; Chakraborty, Debanjan; Haldar, Sattwick; Shelke, Ankita; Ajithkumar, Thalasseril G.; Vaidhyanathan, Ramanathan (Nanoscale Horizons, 2023)
Adaptable polymer-based solid-state electrolytes can be a game-changer toward safe, lightweight flexible batteries. We present a robust Bakelite-type organic polymer covalently decked with viologen, triazine, and phenolic moieties. Its flexible structure with cationic viologen centers incorporates counter-balancing free hydroxide ions into the polymeric framework. By design, the aromatic groups and heteroatoms in the framework can be activated under an applied potential to prompt a push-pull drive, setting off the towing of hydroxide ions via weak electrostatic, van der Waals, and hydrogen-bond interactions. The frontier orbitals from a DFT-modeled structure certify this. The hydroxyl-polymer requires minimal KOH wetting to maintain a humid environment for Grotthuss-type transport. The hydroxide ion conductivity reaches a value of 1.4 x 10(-2) S cm(-1) at 80 degrees C and 95% RH, which is retained for over 15 h. We enhanced its practical utility by coating it as a thin solid-state separator-cum-electrolyte on readily available filter paper. The composite exhibits a conductivity of 4.5 x 10(-3) S cm(-1) at 80 degrees C and 95% RH. A zinc-air battery (ZAB) constructed using this polymer-coated paper as electrolyte yields a maximum power density of 115 mW cm(-2) and high specific capacitance of 435 mA h g(-1). The power density recorded for our ZAB is among the best reported for polymer electrolyte-based batteries. Subsequently, the flexible battery fabricated with IISERP-POF11_OH@FilterPaper exhibits an OCV of 1.44 V, and three batteries in series power a demo traffic signal. To underscore the efficiency of hydroxide ion transport through the complex multifunctional backbone of the polymer, we calculated the diffusion coefficient for OH- (Exp: 2.9 x 10(-5) cm(2) s(-1); Comp. 5.2 x 10(-6) cm(2) s(-1)) using electrochemical methods and MD simulations. Climbing-edge NEB calculations reveal a large energy barrier of 2.11 eV for Zn2+ to penetrate the polymer and identify hydroxide ions within the polymer, suggesting no undesirable Zn2+ crossover. Our findings assert the readily accessible C-C-linked cationic polymer's capacity as a solid-state electrolyte for ZABs and any anion-conducting membrane.

Made to measure squaramide COF cathode for zinc dual-ion battery with enriched storage via redox electrolyte - Kushwaha, Rinku; Jain, Chitvan; Shekhar, Pragalbh; Rase, Deepak; Illathvalappil, Rajith; Mekan, Deep; Camellus, Augastus; Vinod, Chathakudath Prabhakaran; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2023)
Aqueous rechargeable batteries are promising grid-scale energy storage devices because of their affordability, operational safety, and environmental benignity. Among these, Zn-ion batteries (ZIBs) have unfolded new horizons. Designing superior cathodes for ZIBs is crucial. Covalent organic frameworks (COFs) can be made redox active with a high storage surface. Here, for the first time, a chelating COF with redox-active ZnI2 in a ZnSO4(aq) electrolyte is combined. Including iodide harvests an approximately threefold enhancement in capacity from 208 to 690 mAh g(-1) at 1.5 A g(-1), the highest among all the COF-derived ZIBs. Remarkably, a charge-discharge curve at 1.3 V exhibits very limited dropout voltage and super-flat platform, with a remarkable capacity of 600 mAh g(-1) at 5 A g(-1) stable up to 6000 cycles, confirming that the polyiodide generation and storage are sustainable. The COF's dual-ion storage (Zn2+ and polyidode) delivers a ZIB with the highest energy density. Spectro-electrochemical measurements coupled with X-ray photoelectron spectroscopy unambiguously unveil the existence of multiple polyiodide species, with I-3(-) and IO3- ions as the prominent species. The latter gets reduced at the COF electrode under an applied potential, leaving I-3(-) as the major species stored on the COF. The prospect of COF-polyiodide((aq)) is a windfall for metal-ion batteries.
Keywords: covalent organic frameworks; flexible batteries; polyiodide; redox electrolytes; Zn ion batteries

Tailoring COFs: transforming nonconducting 2D layered COF into a conducting quasi-3D architecture via interlayer knitting with polypyrrole - Jain, Chitvan; Kushwaha, Rinku; Rase, Deepak; Shekhar, Pragalbh; Shelke, Ankita; Sonwani, Disha; Ajithkumar, Thalasseril G.; Vinod, Chathakudath Prabhakaran; Vaidhyanathan, Ramanathan (Journal of the American Chemical Society, 2023)
Improving the electronic conductivity and the structural robustness of covalent organic frameworks (COFs) is paramount. Here, we covalently cross-link a 2D COF with polypyrrole (Ppy) chains to form a quasi-3D COF. The 3D COF shows well-defined reflections in the SAED patterns distinctly indexed to its modeled crystal structure. This knitting of 2D COF layers with conjugated polypyrrole units improves electronic conductivity from 10(-9) to 10(-2 )S m(-1). This conductivity boost is affirmed by the presence of density of states near the Fermi level in the 3D COF, and this elevates the COF's valence band maximum by 0.52 eV with respect to the parent 2D pyrrole-functionalized COF, which agrees well with the opto-electro band gaps. The extent of HOMO elevation suggests the predominant existence of a polaron state (radical cation), giving rise to a strong EPR signal, most likely sourced from the cross-linking polypyrrole chains. A supercapacitor devised with COF20-Ppy records a high areal capacitance of 377.6 mF cm(-2), higher than that of the COF loaded with noncovalently linked polypyrrole chains. Thus, the polypyrrole acts as a ``conjugation bridge'' across the layers, lowering the band gap and providing polarons and additional conduction pathways. This marks a far-reaching approach to converting many 2D COFs into highly ordered and conducting 3D ones.
Keywords: covalent organic frameworks; Electrical conductivity

Resorcinol-Azodianiline Covalent Organic Framework Supported FeOOH Quantum Dot-Catalyzed Electrochemical Ammonia Synthesis under Ambient Conditions - Shekhar, Pragalbh; Kosugi, Kento; Singh, Himan Dev; Kushwaha, Rinku; Rase, Deepak; Matsuzaki, Takumi; Jain, Chitvan; Singh, Piyush; Singh, Yashraj; Vinod, Chathakudath Prabhakaran; Kondo, Mio; Masaoka, Shigeyuki; et al. (CHEMISTRY OF MATERIALS, 2024)
Keywords: conversion; nitrogen; Recent Progress; reduction